DEMONSTRATION OF THEM PROTEININ CULTURE FILTRATES OF HEMOLYTIC STREPTOCOCO OF GROUP A - OLARTE, JORGE (INSTITUTO DE ENFERMEDADES TROPICALES, CD. MEXICO, DF, MEX, 1970)
1. Both type specific T and M proteins have been demonstrated in filtrates from heavy cultures of certain strains of Group A hemolytic streptococci grown in peptone-containing media. 2. M-protein concentrated and partially purified from the culture supern
J IMMUNOL
Keywords: DEMONSTRATION, PROTEININ, CULTURE, HEMOLYTIC, STREPTOCOCO; CIENCIAS MEDICAS; OTRAS ESPECIALIDADES MEDICAS (ESPECIFICAR); MEDICINA BIOQUIMICA